The impact of scenario-based simulation training on nursing students’ knowledge and performance in patient care after coronary artery surgery - Elahe Maddahi; Hossein Akbari; Mahdieh Sabery (BMC Nursing)
Abstract Background Coronary artery bypass graft (CABG) surgery is one of the most effective treatments for coronary artery disease. Despite its many benefits, this surgery can also lead to potential complications. Studies have shown that nurses play an important role in managing these complications. Studies have shown that nurses play an important role in controlling these complications. Conventional nursing education often fails to prepare graduates for employment in complex and evolving clinical environments like cardiac wards. Meanwhile, scenario-based learning has recently emerged as a valuable educational method in the clinical training of healthcare professionals. Therefore, this study aimed to determine the effect of scenario-based learning on nursing students’ knowledge and performance in patient care after coronary artery surgery at Kashan University of Medical Sciences. Methods The present study used a pretest-posttest design in 2024(April to December), with the research population consisting of fifty nursing students of Kashan University of Medical Sciences. All students were included in the study using convenience sampling method and were randomly assigned to two groups: one receiving conventional training methods and the other participating in scenario-based simulation training. First, the scenarios were written and validated. Data were collected using a demographic questionnaire, a knowledge assessment questionnaire, and a performance assessment checklist. The validity and reliability of the instruments were investigated and confirmed. After data collection, the analysis was conducted using SPSS 16 software, with a significance level of 0.05. Results According to the study results, a significant increase was observed in the performance scores of nursing students in patient care after coronary artery surgery after receiving the training (P < 0.05). However, the change in the knowledge score was not significantly different between the two groups (P < 0.05). The results of the independent T-test showed no significant difference in the change in knowledge score between the two groups. But the increase in performance score between the two groups was significant (P < 0.05). The results of the ANCOVA test showed that the type of training had no effect on the change in knowledge scores (P = 0.301) but significantly affected the change in performance scores (P = 0.036). Conclusion Given the effectiveness of scenario-based simulation training, it is recommended that this method be used in the clinical education of nursing students and nurses.